The Development of Bio-Briquettes from Agricultural Waste as an Alternative Fuel of Gas and Kerosene - Mandey, Lucia C.; Tarore, Dantje (Pascasarjana Unsrat, 2015)
This study was aimed to utilize rice husk and corn cob and skin to produce biobricket as an alternative to kerosene and gas through examination of caloric value and ash content of the rice husk, corn cob, corn skin and biobricket combustion characteristics. The study used an experimental method to reexamine the quality of biobricket in laboratory and field. The former started with charcoal furnace preparation and rendement calculation of the rice husk and corn skin charcoal produced. The charcoal quality test was examined through caloric and ash level valuation. The biobricket quality was based upon size variations, 15 mesh, 20 mesh, 25 mesh, 30 mesh and pressure through compression process using a hydrolic pump of 5000 kg/m2. The rice husk and corn skin was collected from North Minahasa Regency. Variables observed in the study were charcoaling process using a furnace covering rendement output (%). charcoaling duration (minute), maximum charcoal temperature (oC), and caloric value (cal/g) and ash content (%) of the charcoal tested in the laboratory of Research and Industrial Standardization Board, Manado. The biobricket quality characteristic obtained was boiling time.The highest water boiling time occurred in 15 mesh size in 27 minutes, maximum temperature under the pan, 383oC in 30 mesh, duration of 562 minutes of biobricket charcoal burnt out in 30 mesh and the best (least) ash combustion remain of the biobricket charcoal of 12.48% in treatment 15 mesh. The agricultural wastes, as rice husk and corn skin, could be produced as environmental friendly biobricket with the best treatment of 15 mesh size that resulted in the highest boiling duration and the least ash residue, and the treatment of 30 mesh size gave maximum temperature under the pan and the longest time of burnt out biobricket charcoal. Keywords : bio-briquettes, rice husk, corn skin